The locked room mystery in the works by Edgar Allan poe, sir Arthur Conan doyle and Agatha Christie - Reis, Raíza dos (Universidade do Vale do Rio dos Sinos, 2020)
The aim of this paper is to compare three detective stories from different periods of time by analyzing their similarities and differences concerning structure. To undertake this study, three detective stories were chosen: “The Murders in the Rue Morgue” (1841) by Edgar Allan Poe, “The Speckled Band”, (1892) by Arthur Conan Doyle and A Holiday for Murder (1938) by Agatha Christie. These three detective stories were chosen because all of them are part of the Crime Fiction subgenre the Locked Room Mystery. The aim is to verify the similarities and differences among them, since they might follow the same pattern, even though being written in different eras: Romanticism, Victorian and Georgian Literature.
Keywords: Detective stories; Locked Room Mystery; Literature; Histórias de detetive; Mistério da sala trancada; Literatura